A Literature Review: Strategies on Youth Violence - Singh Birhman, Himani; Vasudev, Kavita; Singh Birhman, Anshu (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The current literature review was done to make an account of Youth Violence and its preventive strategies. Youth Violence is an increasing concern of our society and is surprisingly growing each passing day. Its growth lies beneath the development of the individual. The numerous factors nurturing it are also the parts of the society and know the least to minimize or help the individual to overcome it. Also, many of the interventions do not end up being fruitful as they are not designed to fit the needs of the individual. This study covers strategies that are carefully picked and selected by their effectiveness to prevent youth violence. These strategies will help to empower each member of the society to help the individual to overcome the issue and thereby contributing to create peaceful and healthy environment.